"Sedimentological characteristics, provenance and hydrocarbon potential of Post Santonian sediments in Anambra Basin, Southeastern Nigeria " (2012)
"Field studies of outcrop samples from part of Anambra basin, southeastern Nigeria, were investigated to unravel the lithofacies distribution, provenance, palaeotectonic history as well as aspects of hydrocarbon potential of the basin. The sandstone facies of the Nkporo, Owelli, Mamu and Ajali Formations are cross bedded, medium to coarse grained, poorly sorted to moderately well sorted, negatively skewed and leptokurtic to platykurtic. Textural plots and multivariate parameters indicate fluvial to shallow marine environment. Paleocurrents signify southwest direction for the Nkporo and Ajali Formations while the Owelli Formation points to a northwest direction. The sandstones classify as quartz arenite with heavy mineral assemblages that revealed the presence of zircon, rutile, tourmaline, staurolite, sillimanite, kyanite, garnet and apatite; having ZTR index of 63 %. These typify products of weathering of basement rocks under humid climatic setting with long transportation and/or recycling history. Organic matter quantity of the shales ranges from mass fractions 0.89 % to 3.98 % TOC and Rock-eval parameters indicate immature, poor to fair hydrocarbon potential. Cross plots of rock eval parameters revealed gas proned terrestrially derived Types III and IV kerogen. It can be deduced that the sandstones were sourced from the Adamawa–Abakaliki folded belt and part of Oban Massif while the shales have prospect to generate gas at appropriate maturation, especially from the Nkporo Shale. "